Atlantic forest fragmentation and genetic diversity of an isolated population of the Blue-manakin, Chiroxiphia caudata (Pipridae), assessed by microsatellite analyses - Francisco, Mercival R.; Galetti, Mauro [UNESP]; Galetti Jr., Pedro Manoel (My University, 2006)
Habitat fragmentation is predicted to restrict gene flow, which can result in the loss of genetic variation and inbreeding depression. The Brazilian Atlantic forest has experienced extensive loss of habitats since European settlement five centuries ago, and many bird populations and species are vanishing. Genetic variability analysis in fragmented populations could be important in determining their long-term viability and for guiding management plans. Here we analyzed genetic diversity of a small understory bird, the Blue-manakins Chiroxiphia caudata (Pipridae), from an Atlantic forest fragment (112 ha) isolated 73 years ago, and from a 10,000 ha continuous forest tract (control), using orthologous microsatellite loci. Three of the nine loci tested were polymorphic. No statistically significant heterozygote loss was detected for the fragment population. Although genetic diversity, which was estimated by expected heterozygosity and allelic richness, has been lower in the fragment population in relation to the control, it was not statistically significant, suggesting that this 112 ha fragment can be sufficient to maintain a blue-manakin population large enough to avoid stochastic effects, such as inbreeding and/or genetic drift. Alternatively, it is possible that 73 years of isolation did not accumulate sufficient generations for these effects to be detected. However, some alleles have been likely lost, specially the rare ones, what is expected from genetic drift for such a small and isolated population. A high genetic differentiation was detected between populations by comparing both allelic and genotypic distributions. Only future studies in continuous areas are likely to answer if such a structure was caused by the isolation resulted from the forest fragmentation or by natural population structure.
Keywords: Birds; Forest fragmentation; Genetic variability; Manakins; allele; genetic analysis; genetic differentiation; genetic drift; genetic variation; genotype; habitat fragmentation; heterozygosity; human settlement; isolated population; passerine; population structure; spatial distribution; stochasticity; Atlantic Forest; South America; Aves; Chiroxiphia caudata; Pipridae